2014
DOI: 10.1128/mcb.00457-14
|View full text |Cite
|
Sign up to set email alerts
|

FANCD2-Controlled Chromatin Access of the Fanconi-Associated Nuclease FAN1 Is Crucial for the Recovery of Stalled Replication Forks

Abstract: Fanconi anemia (FA) is a cancer predisposition syndrome characterized by cellular hypersensitivity to DNA interstrand cross-links (ICLs). Within the FA pathway, an upstream core complex monoubiquitinates and recruits the FANCD2 protein to ICLs on chromatin. Ensuing DNA repair involves the Fanconi-associated nuclease 1 (FAN1), which interacts selectively with monoubiquitinated FANCD2 (FANCD2(Ub)) at ICLs. Importantly, FANCD2 has additional independent functions: it binds chromatin and coordinates the restart of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(91 citation statements)
references
References 51 publications
(114 reference statements)
5
75
0
Order By: Relevance
“…After HU and APH treatment, Rad51 loaders, such as BRCA2, prevent Mre11-dependent nucleolytic degradation of nascent DNA at stalled replication forks (6,7,(9)(10)(11)(12)(13)(14)38). We therefore treated Rad51-depleted and control samples with mirin, a specific inhibitor of the exonuclease activity of Mre11 (39).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After HU and APH treatment, Rad51 loaders, such as BRCA2, prevent Mre11-dependent nucleolytic degradation of nascent DNA at stalled replication forks (6,7,(9)(10)(11)(12)(13)(14)38). We therefore treated Rad51-depleted and control samples with mirin, a specific inhibitor of the exonuclease activity of Mre11 (39).…”
Section: Resultsmentioning
confidence: 99%
“…Over the past few years, it has become evident that Rad51 escorts ongoing replication forks regardless of the presence of DSBs (3)(4)(5). Specifically, Rad51 protects persistently stalled replication forks from Mre11-mediated nucleolytic degradation and facilitates replication fork restart when the replication-halting agent hydroxyurea (HU) or aphidicolin (APH) is removed (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Such novel functions of Rad51 require many HRR factors, including BCRA2, FANCD2 (Fanconi Anemia Complementation group protein D2), CtIP, BRCA1, and the WRN helicase, but are independent of HRR effectors, such as Rad54 (6,7).…”
mentioning
confidence: 99%
“…In yeast, Fan1 is capable of conferring ICL repair activity in the absence of the UBZ domain (Fontebasso et al 2013). One potential role of the interaction between FAN1 and FANCD2/FANCI outside of ICL repair includes the processing of replication forks under normal or replicative stress conditions (Schlacher et al 2012;Chaudhury et al 2014;Chen et al 2015). Most recently, it has been shown that the UBZ domain of FAN1 is essential for the processing of replication forks and protection against chromosome instability after treatment with HU and MMC (Lachaud et al 2016).…”
Section: Fan1 and Icl Repairmentioning
confidence: 99%
“…The current model proposes that DNA2 and MRE11 accumulate on different types of stalled forks depending on their structures and the moment at which they appear (Karanja et al 2014, Higgs et al 2015, Thangavel et al 2015. Nevertheless, the recent finding that the Fanconi-associated nuclease 1 (FAN1) is also implicated in replication fork recovery (Lachaud et al 2016, Chaudhury et al 2014 suggests that this model is much more complex than initially anticipated.…”
Section: Brca2 Protects Stalled Replication Forks From Nucleolytic Dementioning
confidence: 67%